HUBUNGAN PERILAKU DAN SIKAP PERAWAT TERHADAP UPAYA PENCEGAHAN HAIS DI RUANG RAWAT INAP RSUD MAYJEND HM RYACUDU KOTA BUMI LAMPUNG UTARA TAHUN 2020 - Arifki Zainaro; Ricko Gunawan; Mardani Mardani (Jurnal Ilmu Keperawatan Indonesia, 2021)
The ability of nurses to prevent infection in puskesmas and prevention efforts is the first level in providing quality services. Nurses must play a role in preventing infection with HAIs, this is because the nurse is a member of the health team who deals directly with clients / patients and infectious materials in the puskesmas ward. The nurse is also responsible for maintaining the safety of clients / patients at the health center through prevention of accidents, injuries, trauma, and through the spread of HAIs infection. The purpose of this study was to determine the relationship between nurses' behavior and attitudes towards prevention of HAIs in the Inpatient Room of the Mayjend HM Ryacudu Hospital, Kota Bumi, North Lampung Regency, 2020The type of research used in this research is quantitative with design used an analytical cross-sectional approach. The population, were all nurses in the inpatient room of RSUD Mayjend HM Ryacudu Kota Bumi, North Lampung Regency, totaling 92 people and   the sample in this study amounted to 92 people. In this study the sampling technique used was the total population, this is because the available respondents were <100 respondents.It  is  known  that  at  the  Mayjend  HM  Ryacudu  Kotabumi  Hospital,  North  Lampung Regency in 2020, most of the respondents had bad behavior totaling 52 respondents (56.5%), most of the respondents had negative attitudes totaling 57 people (62.0%) and most of therespondents had bad HAIs prevention efforts totaling 51 respondents (55.4%).There is a Relationship between Nurse Behavior and Attitudes Towards Prevention of HAIs in the Inpatient Room of RSUD Mayjend HM Ryacudu Kota Bumi, North Lampung Regency in 2020. The results of this study are expected to be input for RSUD regarding the behavior and attitudes of nurses in making efforts to prevent HAIs, with the mandatory way to apply the use of PPE is good, if you don't apply the use of PPE in accordance with the SOP, then sanctions must be given to nurses, evaluate the performance of nurses and provide health knowledge facilities by holding health training or seminars Keywords : Behavior, Attitude of Nurses & Prevention of HAIs